Noise Suppression in ECG Signals through Efficient One-Step Wavelet Processing Techniques - E. Castillo; D. P. Morales; A. García; F. Martínez-Martí; L. Parrilla; A. J. Palma (Journal of Applied Mathematics)
This paper illustrates the application of the discrete wavelet transform (DWT) for wandering and noise suppression in electrocardiographic (ECG) signals. A novel one-step implementation is presented, which allows improving the overall denoising process. In addition an exhaustive study is carried out, defining threshold limits and thresholding rules for optimal wavelet denoising using this presented technique. The system has been tested using synthetic ECG signals, which allow accurately measuring the effect of the proposed processing. Moreover, results from real abdominal ECG signals acquired from pregnant women are presented in order to validate the presented approach.